Quarantine treatment of hoa loc mango by electron beam irradiation - Nguyen , Thi Ly; Cao , Van Chung; Chu , Nhut Khanh; Pham , Thi Thu Hong; Doan , Binh; Le , Quang Thanh; Vo , Anh Tuan; Nguyen , Duy Ngoc; Ngo , Tuong Vy; Phan , Thi Thu Hien; Ta , Ngoc Tu Quynh; Tcheng , Hoang Nhu Hao; et al. (Nuclear Science and Technology, 2021)
Using electron beam (EB) irradiation as quarantine treatment for fresh fruits in particular and foods of plant origin in general is a growing trend of the world. Our preliminary results on EB irradiation impacts on Hoa Loc mangoes showed that EB irradiation could be a suitable quarantine treatment for the Hoa Loc mango fruits having weight from 407 to 552g and thickness from 7.3 to 8.0 cm to ensure the dose uniformity ratio (DUR) among irradiated products is within limitation (DUR ≤ 2.5). Main quality parameters of irradiated mangoes were insignificantly affected by exposure to EB with the dose ranging from 0.4 to 0.8 kGy, though their weight loss, the color indices L* (lightness), a* (redness to greenness), b* (yellowness to blueness) and firmness were slightly changed in compared with the control (non-irradiated). The results also revealed that vitamin C concentration of the fruits irradiated at 1 kGy much reduced and the hue angle significant increased by the end of storage. These results suggested that EB irradiation of Hoa Loc mangoes at the generic doses of 0.4 kGy is a feasible quarantine treatment that maintains the main the fruit quality.